The Analysis of the Effect of Academic Service Quality on Student Loyalty Through Student Satisfaction and Organizational Performance - Muhammad Ajir Muzakki; Zeplin Jiwa Husada Tarigan (Master of Management, School of Business and Management, Petra Christian University, 2020)
This research aims to analyze the significant influence of quality academic services to student loyalty with student satisfaction and organizational performance as intervening. The sample in this study as many as 40 people, data collection using questionnaires, and then analyzed with SEM PLS using smart software PLS 3.0. Based on the results of the analysis show that the quality of academic services has an effect on student loyalty with a statistical t-value of 2.532, the quality of academic services has no effect on organizational performance with a statistical value of 0.026, the quality of academic services has an effect on student satisfaction with a value of 1.988 statistics, student satisfaction has an effect on organizational performance with a t-value of 1.891, student satisfaction has no effect on student loyalty with a statistical t-value of 0.370, organizational performance influences student loyalty with a statistical T value of 8.380, student satisfaction does not mediate the effect of academic service quality with a statistical t-value of 1.201, student satisfaction does not mediate the effect of academic service quality on student loyalty with a statistical t-value of 0.319, organizational performance mediates the effect of student satisfaction on student loyalty self with a statistical t-value of 1.778, student satisfaction and organizational performance does not mediate the effect of academic service quality on student loyalty with a statistical t-value of 1.169, organizational performance does not mediate the effect of academic service quality on student loyalty with a statistical T value of 0.025.